Evaluation of Website Prototype Based on Basic Ui/Ux Principles (Case Study: Eigen Natur Indo) - Triani, Ananda Risya; Rahman, Yanuar (Universitas Multimedia Nusantara, 2024)
Abstract: In this digital era, businesses both on a small and large scale are required to be able to keep up with developments and utilize digital technology (digital platform), especially in sales and marketing activities for product or service, for example a website. Just like PT. Eigen Natur Indo, which continues to follow technological developments to be able to increase its sales and marketing activities, namely through marketplaces, social media, and websites. The website is a medium that is currently being developed in prototype, in the future the use of the website as a medium for product transactions for customers (e-commerce) and advertising. However, no evaluation has been carried out, especially to end users. To produce an optimal website, it is necessary to apply the principles of user interface (UI) and user experience (UX). So in this research, an evaluation of the Eigen Natur Indo website prototype was carried out based on the basic principles of UI and UX. The research method used is a qualitative method, which is based on data from observation, interview, and analysis, including usability testing activities. The user test involved five end users who were asked to run certain scenarios on the prototype website, and then evaluated and interviewed the users regarding the problems faced on the interface. In general, findings or insights were obtained that can be used as recommendations for website development, namely the need for more effective user flow, certain navigation with shapes and sizes that are more recognizable and consistently placed, the selection of appropriate design elements, and the addition of notification features. Keywords: prototype; website; user interface; user experience; usability testing.